High-Resolution Hybrid Hardware Implementation of DOA Estimation Using MVDR and MUSIC Algorithms on RFSoC Gen 3 Platform - Efimov, Sergei; Ginzberg, Yuval; Cohen, Emanuel (IEEE ... International New Circuits and Systems Conference (Online), 2025)
This paper proposes a hybrid architecture for implementing a direction of arrival (DOA) estimation on a Xilinx RFSoC Gen 3 platform by distributing the computational effort between the programmable logic (PL) and the processing system (PS), offering a good balance between fast development time, latency, and accuracy. The system was demonstrated using a four-element linear phased array antenna driving four RFSoC inputs for DOA estimation based on MVDR and MUSIC algorithms at {5.7 ~ \text{GHz}} . Both the MVDR and MUSIC algorithms achieved standard deviation (STD) lower than 0.15° up to ± 30^{°} DOA angle over the air with 2.6 ms latency.